Moral Reasoning and Political Leader Preference of Senior High School Students of a Private School - Goyon, Raymond P.; Legaspi, Carlos Eduardo I. (Philippine Social Science Journal, 2020)
Kohlberg’s moral development theory focuses on the thinking process that occurs when one makes a moral decision. Kohlberg had identified three stages of moral development: Pre-conventional, Conventional, and post-conventional. Moral reasoning, as perceived to be a factor in the decision-making, is a rational act guided by moral principles. It is a subjective evaluation related to practical reasoning, where one justifies the idea based on how a person views various thing. Moreover, decisions rely on reasoning; moral reasoning is related to making a congruent decision when a person creates preference takes more courage in deciding whom to elect during elections. Voting preferences can be affected by certain factors such as peer influence, media influence, family influence, and church/religious community. Political leader preference is described as a judgment based on evaluations and observations through interaction with political content. It may also refer to a political or philosophical opinion on an individual pertained to be a candidate for leadership. Like the Senior High School (SHS) students, some new voters are easily swayed by some politicians. The purpose of this study is to determine the level of moral reasoning and the degree of preference for a political leader of SHS students when grouped according to sex, family monthly income, age, and church ministry involvement. Specifically, it also compares the degree of preference for political leaders when grouped according to variables and correlates moral reasoning and preference for political leaders. Likewise, it explores other factors that influence the political leaders’ preference.